Potential Application of Bionanoparticles to Treat Severe Acute Respiratory Syndrome Coronavirus-2 Infection - Debnath, Sujit K.; Srivastava, Rohit (Frontiers in Nanotechnology, 2022)
Severe acute respiratory syndrome coronavirus-2 (SARS-CoV-2) is a contagious virus that spreads exponentially across the world resulting in serious viral pneumonia. Several companies and researchers put their tremendous effort into the development of novel vaccines or drugs for the complete eradication of COVID-19 caused due to SARS-CoV-2. Bio-nanotechnology serves a vital role in the designing of functionalized biocompatible nanoparticulate systems with higher antiviral capabilities. Thus several nanocarriers have been explored in designing and delivering drugs and vaccines. This problem can be overcome with the intervention of biomaterials or bionanoparticles. The present review describes the comparative analysis of SARS infection and its associated etiological agents. This review also highlighted some nanoparticles that have been explored in the treatment of COVID-19. However, these carriers elicit several problems once they come in contact with biological systems. Often, the body’s immune system treats these nanocarriers as foreign particles and antigens. In this contrast, some bionanoparticles are highlighted here with their potential application in SARS-COV-2. However, bionanoparticles have demonstrated some drawbacks that are discussed here with the possible outcomes. The scope of bioinspired nanoparticles is also discussed in detail to explore the new era of research. It is highly essential for the effective delivery of these nanoparticles to the target site. For effective management of SARS-CoV-2, different delivery patterns are also discussed here.